Meningkatkan Keterampilan Kognitif Anak Usia 5-6 Tahun melalui Eksperimen Sederhana Pembuatan Es Krim di Kober Al-Ibad - Husna, Dewi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Through the use of experimental methods, this research seeks to increase the cognitive capacity of children aged 5-6 years in Kober Al-Ibad in relation to learning and problem solving. Classroom Action Research is the research method used (PTK). The design developed by Kemmis and McTaggart was used in this research. The four steps that make up a cycle are preparation, activity, observation, and reflection. Thirteen second grade students from class B1 Kober Al-Ibad served as study participants. Data collection approach through observation and documentation. Research shows that children's cognitive development occurs in stages. In cycle I, only seven children managed to reach the beginning to develop (MB) stage, while six children were still not sufficiently developed (BB). This relates to mentioning the tools and materials for making ice cream, explaining their function, and carrying out the experiment correctly. In addition, of the 10 children tested, 5 successfully reached the Beginning to Develop (MB) stage due to the accuracy of the ice cream making procedure and their ability to articulate the experimental findings, while the other 8 children remained at the No stage. Undeveloped Stage (BB). In cycle II, things started to improve; At that time, most children had reached the expected developmental stage (BSH), and some even reached the very good developmental stage (BSB). When children's cognitive development improved significantly compared to the first cycle of activities, it was clear that the ice cream experiment had a big impact.